Proceedings of SPE Annual Technical Conference and Exhibition 1993
DOI: 10.2523/26465-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fractal Reservoir Model for Interference Test Analysis in Kamojang Geothermal Field (Indonesia)

Abstract: This paper presents the application of a new concept, i.e.; fractal model, to analyze pressure transient test data in complex naturally fractured geothermal reservoir.Application of conventional type curves has been unsuccesful in analyzing and interpreting the interference te,;l results in Kamojang geothermal reservoir which is considered as a complex naturally fractured system.Using the conventional type curve method, the pressure test data, in this case, can not match to the curve, primarily at early time d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…References [5,6] proposed a seepage model of Newtonian fluid in fractal reservoir and analyzed its well test curve. References [7,8] showed that fractal reservoir seepage model can be explained much more effectively than traditional one and obtained a conclusion very consistent with well test curve. References [9,10] discussed that the fractal theory was powerful in analysis of the fluid flow properties with complex and microscopic stochastic microstructures in porous media.…”
Section: Introductionsupporting
confidence: 57%
“…References [5,6] proposed a seepage model of Newtonian fluid in fractal reservoir and analyzed its well test curve. References [7,8] showed that fractal reservoir seepage model can be explained much more effectively than traditional one and obtained a conclusion very consistent with well test curve. References [9,10] discussed that the fractal theory was powerful in analysis of the fluid flow properties with complex and microscopic stochastic microstructures in porous media.…”
Section: Introductionsupporting
confidence: 57%
“…Single-phase flow in the fractal object was described by an appropriate modification of the diffusivity equation. In addition, the viability of the model in explaining parameters such the transmissibility, storativity and fractal dimension of a complex naturally fractured geothermal reservoir was analyzed through the pressure transient test data (Aprilian et al, 1993). What is more, the fractal theory was applied to real well tests in various fractured reservoirs and the physical meaning of the fractal parameters was presented in the context of well testing in 1995 (Acuna et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Reliability of can be assessed in different ways. The first one is to note that a rough approximation of the derivative of Δp with respect to ln t may be written as follows (assuming t′ α ≈ t α ): This expression, which scales as t α , is equivalent for d = 2 (i.e., α = 1 − D/(2 + θ)) to the one found by approximation of the Chang and Yortsos solution for long times [ Aprilian et al , 1993]. Another possibility is to check the solution against numerical results.…”
Section: Analytical Model and Its Inversion Proceduresmentioning
confidence: 99%